Host-guest complexation toward improving the stability of inverted perovskite solar cells (2023)
ABSTRACT : Hybrid perovskite materials have gained remarkable attention in solar cell research, showcasing a striking increase in efficiency from 3.81% to a world record of 26% over the past decade. Their superior optoelectronic properties, characterized by high absorption coefficients, prolonged carrier lifetimes, and tunable bandgaps, position them favorably for diverse photovoltaic applications. Initially, methylammonium lead triiodide (MAPbI3) dominated perovskite solar cell fabrication, later challenged by formamidinium-based perovskites for their improved thermal stability and narrower bandgaps, especially advantageous for device performance and longevity. Despite advancements, stability remains a challenge, urging extensive research to reduce degradation caused by environmental stressors. Thus, improvement of the intrinsic stability of hybrid perovskite materials is vital for long-term commercial viability of the technology. For this purpose, techniques including passivation, additive engineering and compositional adjustments have been explored. The inverted device architecture (p-i-n) has recently gained attractiveness mainly due to its reduced hysteresis, and lower-temperature fabrication. This study investigates host-guest (HG) complexation employing a crown ether molecule (dibenzo-24-crown-8) as a post-treatment of methylammonium (MA)- and formamidinium (FA)- based perovskite films and as a dopant in the Electron Transport Layer (ETL) of solar cells with p-i-n architecture. Characterization techniques revealed that HG complexation via post-treatment improves the stability of both MA- and FA-based inverted perovskite solar cells. This enhancement arises from the ion binding nature of HG complexation, retarding degradation in critical device components